Identification of broadly-conserved parasitic nematode proteins that activate immunity - Rosa, Bruce A.; Zarlenga, Dante S.; Fournet, Valsin M.; Beshah, Ethiopia; Hill, Dolores E.; Zarlenga, Alexander; Yee, Angela; Liang, Xiaowu; Shandling, Adam D.; Oberai, Amit; Urban, Joseph F.; Mitreva, Makedonka (Frontiers in Parasitology, 2023)
Soil transmitted nematodes are impediments to human health and agricultural production. Poor anthelmintic efficiencies, the emergence of resistant strains, and the persistence of infective stages highlight the need for more effective control strategies. Parasitic nematodes elicit a Th2-type immune response that most often is not protective. Vaccination has thus far been unsuccessful due to unrealized antigenic characters and unknown mechanisms that nematodes use to circumvent host immunity. Here, we used a genomics / proteomics approach (including immunoblot experiments from pigs infected with T. suis) to prioritize putative immunogenic excretory/secretory (E/S) proteins conserved across and specific to several gastrointestinal (GI) parasitic nematode species. A cocktail of five recombinant proteins optimized for conserved GI nematode targets was used immunize pigs and test for active antibody responses in both the serum and intestinal ileal fluid of immunized pigs. An antibody-protein array of putative immunogenic proteins was developed from a combined bioinformatic, experimental, and literature-based prioritization of homologous parasite proteins. Screening the array with sera and ileal fluid samples from immunized pigs suggested cross-reactivity among homologous proteins and a general activation of immunity. PCA clustering showed that the overall immune responses were altered by immunization, but no substantial changes were observed following direct worm challenge with either Ascaris suum or Trichuris suis. Proteins that activated immunity are potential antigens for immunization and the multi-omics phylum-spanning prioritization database that was created is a valuable resource for identifying target proteins in a wide array of different parasitic nematodes. This research strongly supports future studies using a computational, comparative genomics/proteomics approach to produce an effective parasite vaccine.